Effectiveness of the Lontong Balap Program in Population Administration Services in The City of Surabaya Which Requires Court Determination - Arofah, Yayuk Nur; Wibawani, Sri (Publik : (Jurnal Ilmu Administrasi), 2025)
Surabaya City is one of the cities that often launches various innovations in the field of population administration services, namely the Lontong Balap program. The Lontong Balap program is the result of a collaboration between the Population and Civil Registry Office and the Surabaya City District Court which provides various services related to population administration that require a court decision since 2021. In practice, the socialization of the Lontong Balap program is still uneven so that the program's objectives have not been achieved and there is still a lack of Human Resources (HR) in the district court. This study aims to analyze and describe the effectiveness of the Lontong Balap program in population administration services in the city of Surabaya that require a court decision. This research method uses a qualitative descriptive method using the theory of effectiveness with the criteria of program understanding, right on target, on time, achievement of goals, and real change. The results of the study showed that the criteria for understanding the program were still less effective, the criteria for right on target showed that they were still less effective, the criteria for timeliness showed that they were quite effective, the criteria for achieving goals showed that they were still less effective, and the criteria for real change showed that they were still less effective. So the Lontong Balap program is still not effective in making it easier for people to take care of population administration that requires a court decision.